LINGUOPOETICAL INTERPRETATION OF THE CONCEPT "BEAUTY" (Scientific journal of the Fergana State University, 2023)
The article examines the concept of "beauty", its eastern and western interpretations. In the representation of beauty through the symbol of a woman, various and general aspects of beauty standards in the East and in the West are analyzed. The verbalization of the criteria of aesthetic assessment in the language is considered.